An active CMOS optical receiver employing an inductor-less, low-noise and high-gain regulated cascode transimpedance amplifier. (April 2021) - Sadeghi, Sahar; Nayeri, Maryam; Dolatshahi, Mehdi; Moftakharzadeh, Ali
Abstract: This paper deals with a high-gain, active, modified RGC transimpedance amplifier with low noise characteristic operating in a 2.5 ​Gb/s optical receiver. By adding an extra transistor to the booster amplifier of an RGC circuit, and manipulating the trade-off between the frequency bandwidth and transimpedance gain, the transimpedance gain of 60 ​dBΩ is obtained, which reduces the input referred noise and enlarges the SNR of the circuit, while, consumes 760 ​μW power using 65 ​nm CMOS process. The TIA stage, also, occupies a small area due to existence of only five transistors in its structure. The circuit is mathematically analyzed and related simulations justify its proper performance as not only a 2.5Gbps TIA, but also as a 5Gbps TIA. Finally, the presented TIA is followed by three stages of an NMOS-PMOS differential limiting amplifier to test its behavior as a complete 2.5 ​Gb/s optical receiver, which provides 85′704Ω gain with dissipating power of 5 ​mW.